Layered superconductors. Volume 1 - Klemm, Richard A. (Oxford : Oxford University Press, 2012)
This text provides a comparison of the different chemical structures, normal state properties, and simplest superconducting properties of all known classes of layered superconductors.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Superconductors